PERAN MEDIASI CUSTOMER VALUE PADA PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN HOTEL GOLDEN TULIP PONTIANAK - B31112061, Frenzy (Jurnal Manajemen Update, 2016)
Golden Tulip Hotel Pontianak is a 4 star hotel in the city of Pontianak. Company engaged in hospitality services should be able to always maintain a good value in the eyes of consumers. Marketing mix strategies, if executed properly will tend to provide good value and directly improve customer satisfaction, thus making consumers loyal to that hotel. This study aims to analyze how much influence the marketing mix to customer satisfaction through customer value Golden Tulip Hotel Pontianak. Samples in this study was 100 respondents using purposive sampling technique. Model data analysis used is regression Spaced (Path Analysis). Based on the first test using the t test was concluded that the elements of the marketing mix consisting of product variables have a positive effect but not significant customer value, the price variable has a positive effect but not significant customer value, promotion variables have positive and significant impact on customer value, variable location has a positive and significant impact on customer value, variable people (employee) has a positive effect but not significant customer value, physical evidence variable has a positive effect but not significant customer value, the process variables have a positive and significant impact on customer value. The second test using the t test concluded that the variables studied customer value and significant positive effect on customer satisfaction. Keywords: marketing mix, product, price, promotion, location, people (employees), physical evidence, process, customer value, and customer satisfaction